Seeing and Believing: The Relationship between Perception and Mental Verbs in Acquisition. Issue 1 (2nd January 2021) - Davis, E. Emory; Landau, Barbara
ABSTRACT: Perception verbs and mental verbs have significant overlap in their syntax and semantics; both reference mental representations when taking embedded clauses, as in I see that Maria was here and I think that Maria was here . Some have suggested that perception is more accessible for young children than mental states, raising the question of whether perception verbs could serve as a semantic model for the acquisition of mental verbs via their shared syntax. Since embedded clauses are key to referencing mental states for both verb classes, we examine the developmental trajectory of perception vs. mental verbs in these constructions and others. Using a sample of 5, 884 child-produced utterances and 8, 313 parent-produced utterances from the Brown and Gleason corpora of CHILDES, we analyze children's production of perception and mental verbs in their syntactic frames, as well as that of their parents. We find that children begin to produce embedded frames for both perception and mental verbs around the same time, but produce embedded frames with mental verbs more often, especially as they get older, despite greater use of perception verbs overall. These patterns do not reflect parental input: parents produce both verb types with similar frequency and use embedded frames more often than their children. These findings suggest that perception verbs are unlikely to serve as a model for mental verbs, and instead that mental verbs and their regular occurrence with embedded frames may provide a model for perception verbs when the latter reference mental states. We propose a semantic updating account for children's acquisition of perception verbs, arguing that children's early knowledge of perception verbs may not include mental state representations as a component of their meaning, and that this may only develop later as children learn the propositional syntax that is shared by and regularly occurs with mental verbs.